Design and Implementation of Reservation of Parking Spaces Using RFID and GSM technology - Chaudhary, Shrungashri; Kapoor, Mudit (International Journal of Computer Sciences and Engineering, 2015)
In this project a solutions has been provided to the problems encountered during parking a vehicle at commercial parking lots. This problems has been resolved using Parking Reservation System. The Parking Reservation System is an access control and automated Reservation system that provides ID based parking slot provision system. This system is designed for Multiple Dwelling Units (MDU), offices, schools, colleges, Malls, Cinema theaters, Airports, railway station and many more where there is a requirement of a systematic parking reservation of vehicles. The unique identification of the Vehicle entering using RFID tags permits tracking of vehicles entering and exiting the parking premises. It helps the system to know whether the vehicle or its owner is registered so as to prioritize allocation of parking spaces to incoming customers.